THE ROLE OF INFORMATION TECHNOLOGY, BUSINESS ENVIRONMENTAL ADAPTABILITY, ENTREPRENEURIAL ORIENTATION, AND HALAL CERTIFICATION ON THE PERFORMANCE OF HALAL CULINARY MSMES IN WEST JAVA - Emir Izaad Abiyyu Panggabean (Department Islamic Economics, 2025)
This study aims to examine the role of information technology, business environment adaptability, entrepreneurial orientation, and halal certification on the performance of halal culinary MSMEs in West Java. The Slovin technique is used to determine a representative sample size from a population. By using the Slovin formula, researchers can estimate the minimum sample size required to achieve accurate and general research results. The number of respondents studied was 100 respondents who were analyzed using SEM-PLS (Strutural Equation Modeling) and the SmartPLS application version 4.1.0.9. The results of this study indicate that the variables of business environment adaptability and information technology were found to have a positive and significant effect on the performance of halal culinary MSMEs in West Java. Overall, the variable of business environment adaptability is very dominant and has a positive and significant effect on the performance of halal culinary MSMEs in West Java.